Mn-Cu Transmetalation as a Strategy for the Assembly of Decoupled Metal-Organic Networks on Sn/Cu(001) Surface Alloys - Machain, Paloma (2020)
Surface alloying of Cu(001) by Sn deposition is a finely controllable method of tuning the degree of copper reactivity in order to drive the on-surface assembly and synthesis of metal-organic coordination networks. In this work we show that the (32×2)R45° reconstruction of the Sn/Cu(001) surface alloy acts as a weakly interacting substrate ideal for the assembly of rectangular metal-organic networks based on transition metals. As a demonstration, we have grown a two-dimensional coordination network formed by manganese and TCNQ (7,7,8,8-tetracyanoquinodimethane) with 1:1 stoichiometry. In contrast with the same structure grown on Au(111), the use of the Sn/Cu(001) substrate enables a commensurate structure with larger and more regular ordered domains. We show that the formation of a Cu-TCNQ coordination network and subsequent Mn-Cu transmetalation reactions are the key steps of the growth mechanism. Moreover, ab initio density-functional calculations indicate that the system studied in the present work is a unique example of a metal-organic coordination network weakly interacting with the substrate.